The molten glass sewing machine. (3rd April 2017) - Brun, P.-T.; Inamura, Chikara; Lizardo, Daniel; Franchin, Giorgia; Stern, Michael; Houk, Peter; Oxman, Neri
Abstract : We present a fluid-instability-based approach for digitally fabricating geometrically complex uniformly sized structures in molten glass. Formed by mathematically defined and physically characterized instability patterns, such structures are produced via the additive manufacturing of optically transparent glass, and result from the coiling of an extruded glass thread. We propose a minimal geometrical model—and a methodology—to reliably control the morphology of patterns, so that these building blocks can be assembled into larger structures with tailored functionally and optically tunable properties. This article is part of the themed issue 'Patterning through instabilities in complex media: theory and applications'.